(untitled) (Medical Forum Monthly, 2024)
Objective: Varicella zoster virus (VZV)-related disease, particularly herpes zoster, is important infective viral complication of renal transplantation due to long-term immunuo suppression. In our study we examined the clinical presentation, prevalence and outcome of herpes zoster virus in post renal transplant patients. Study Design: Retrospective / cross-sectional study Place and Duration of Study: This study was conducted at the Institute of Kidney Diseases Peshawar (both as in-patient and out-patient department) from August, 2010 to July, 2018. Materials and Methods: A cross-sectional retrospective study design was followed in this research in which medical record files of all the patients who underwent renal transplant at Institute of Kidney Diseases (IKD) Peshawar were reviewed. Results: n=8 subjects (3.33%) developed herpes zoster during a follow-up of 8 years post-transplant. Mean time to the development of VZV infection was 2.27 years (ranging from 06 month to 4.16 years).All patients in cohort had presented with single dermatomal distribution of lesions, none of the patients developed disseminated disease or post herpetic neuralgia. Conclusion: VZV is a common complication after renal transplantation, but in our study the prevalence was very low i.e. 3.3%. Prompt diagnosis and treatment prevent the complication of VZV and visceral disease. Pre transplant active immunization for VZV negative patients should be done to prevent VZV infection